NYADRAN TRADITION IN PULOKULON GROBOGAN: A FORM OF CULTURAL PRESERVATION AND STRENGTHENING LOCAL IDENTITY - Fita Puji Mutnaim; Dita Zakiyatul Lathifa; Dany Miftah M. Nur (International Journal of Multidisciplinary Reseach, 2025)
The Nyadran tradition in Pulokulon, Grobogan is a religious ritual that has been passed down from generation to generation and serves to preserve culture and strengthen local identity. In this tradition, the community performs a series of activities such as cleaning ancestral graves, sowing flowers, and praying together, which reflects the value of mutual cooperation and togetherness. This research aims to describe the implementation of the tradition and understand the cultural values contained in it. By preserving Nyadran, the younger generation is expected to appreciate cultural heritage and strengthen local identity in the midst of changing times.